Socio economic characteristics of milk producers of irrigated and rainfed areas of Visakhapatnam district of Andhra Pradesh - M. Hanna Kumari; M. Kalyana Chakravarthi; K. Sarjan Rao; K. Sakunthala Devi; C. Anil Kumar (Indian Journal of Animal Production and Management, 2022)
A survey was conducted to know the socio economic characteristics of milk producers of irrigated and rainfed areas of Visakhapatnam district of Andhra Pradesh. The data pertaining to the socioeconomic characteristics of 200 dairy farmers from 50 different villages were collected by using a pretested questionnaire through personal interview and the data were analysed. The study revealed that an overall 12.50, 74.50 and 13.00 per cent of respondents were found to be young age, middle age and old age, respectively, in the study area. An overall 17.5, 1.5, 29.5 and 51.50 per cent belonged to scheduled caste, scheduled tribe, backward caste and other caste, respectively in the study area. Most of the milk producers were literate ranging from primary to graduation level of education, out of which majority of them had high school education in irrigated and rainfed areas. Majority of milk producers in Visakhapatnam district had agriculture as main occupation while dairying as subsidiary occupation. Most of the milk producers were of small farmers followed by landless, marginal, medium and large farmers with small family size. Majority of milk producers had extension contact with veterinarians followed by para veterinarians and had mass media exposure with television and radio to get information about dairying.